Perancangan Alat Dan Pengujian Tegangan Tembus Dengan Minyak Isolasi RBDPO Olein Menggunakan Elektroda Bola-Bola - Rudi Setiawan; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The crude oil based transformer insulation has several issues i.e. non-environment friendly, non-biodegradable, non-reneweble, and rarely. Vegetable oil is an alternative transformer insulation which is Crude Palm Oil based RBDPO Olein. This paper proposes study to investigate characteristic the AC breakdown voltage referring to IEC 60156-95 standard to apply sphere electrode of RBDPO Olein prior water content reduction, post water content reduction, and converting fatty acids into Methyl Ester. Breakdown voltage also look into the effect of gap electrode and affectivity of sphere electrode scheme. The experiment has shown the breakdown voltage have increased significantly after various samples of RBDPO Olein being reduction the water content, has compered to IEC 156 standard with the value of (30 kV/2.5 mm). The gap of electrode has shown a significant value on breakdown voltage measurement result. In the mean time to measure the effectivity breakdown voltage of sphere electrode scheme, the Mineral Oil is deployed with complied to IEC 156 standard. The measurement result shows lower then IEC 60156-95 standard was 68,73 %. The experiment also shown the density measurement, the viscosity measurement, the dissolved gas analysis measurement, and dielectric dissipation factor measurement achieve RBDPO Olein less water concentration.Keywords: RBDPO Olein, Breakdown Voltage, Sphere Electrode, IEC 156 standard, and IEC 60156-95 standard.